A Prospective, Randomized Comparison of Duodenoscope Reprocessing Surveillance Methods - Travis J. De Wolfe; Nasia Safdar; Megan Meller; John Marx; Patrick R. Pfau; Eric M. Nelsen; Mark E. Benson; Anurag Soni; Mark Reichelderfer; Megan Duster; Deepak V. Gopal (Canadian Journal of Gastroenterology and Hepatology)
Duodenoscope use in healthcare facilities has been associated with transmission of multidrug resistant pathogens between patients. To assist healthcare facilities in monitoring the quality of their duodenoscope reprocessing procedures and limit patient risk of infection, the Centers for Disease Control and Prevention (CDC) deployed voluntary interim duodenoscope sampling and culturing surveillance protocols in 2015. Though the interim methods were widely adopted, alternative surveillance protocols were developed and implemented at individual institutions. Here, we compared two sampling methods—the 2015 CDC interim protocol and an alternative protocol developed by the University of Wisconsin Hospitals and Clinics (UWHC). We hypothesized that the UWHC protocol would detect a higher incidence of bacterial contamination from reprocessed duodenoscopes. A total of 248 sampling events were performed at UWHC. The CDC protocol (n = 129 sampling events) required culturing samples collected from each duodenoscope after brushing its terminal end and flushing its lumen with sterile water. The UWHC protocol (n = 119 sampling events) required culturing samples collected from each duodenoscope after swabbing its elevator, immersing its terminal end into broth and flushing its lumen with saline. With the CDC method, 8.53% (n = 11) of the duodenoscopes sampled were positive for bacterial growth with 15 isolates recovered. Using the UWHC method, 15.13% (n = 18) of cultures were positive for bacterial growth with 20 isolates recovered. The relative risk of identifying a contaminated duodenoscope using the CDC interim method, however, was not different than when using the UWHC protocol. Mean processing time (27.35 and 5.11 minutes, p<0.001) and total cost per sample event ($17.87 and $15.04) were lower using the UWHC method. As the UWHC protocol provides similar detection rates as the CDC protocol, the UWHC method is useful, provided the shorter processing time and lower cost to perform.